Peran Kepemimpinan Kepala Sekolah dan Lingkungan Kerja dalam Meningkatkan Kinerja Guru PAI di SMA Islam Parlaungan, Waru, Sidoarjo - Maulana, Hanif Indra; Yuliastutik, Yuliastutik; Marfiyanto, Tri (YASIN, 2025)
This research aims to analyze the role of the principal's leadership and work environment in improving the performance of Islamic Religious Education (PAI) teachers at Parlaungan Waru Sidoarjo Islamic High School. Effective leadership and a conducive work environment are considered two key factors that can influence teacher performance, which in turn will impact the quality of education provided to students. The research method used is a qualitative method with a descriptive approach. Data was collected through a questionnaire distributed to all PAI teachers at Parlaungan Waru Islamic High School, Sidoarjo. The research results show that the principal's inspirational and participatory leadership and a supportive work environment have a significant positive correlation with increasing teacher performance. The conclusions of this research emphasize the importance of the leadership role of school principals who are able to motivate and direct and the need to create a comfortable and professional work environment to support the optimal performance of teachers. Recommendations are given to the school to continue to improve the quality of leadership and work environment in order to achieve better educational outcomes.